Escape From X-Chromosome Inactivation: An Evolutionary Perspective - Posynick, Bronwyn J.; Brown, Carolyn J. (Frontiers in Cell and Developmental Biology, 2019)
Sex chromosomes originate as a pair of homologus autosomes that then follow a general pattern of divergence. This is evident in mammalian sex chromosomes, which have undergone stepwise recombination suppression events that left footprints of evolutionary strata on the X chromosome. The loss of genes on the Y chromosome led to Ohno’s hypothesis of dosage equivalence between XY males and XX females, which is achieved through X-chromosome inactivation (XCI). This process transcriptionally silences all but one X chromosome in each female cell, although 15–30% of human X-linked genes still escape inactivation. There are multiple evolutionary pathways that may lead to a gene escaping XCI, including remaining Y chromosome homology, or female advantage to escape. The conservation of some escape genes across multiple species and the ability of the mouse inactive X to recapitulate human escape status both suggest that escape from XCI is controlled by conserved processes. Evolutionary pressures to minimize dosage imbalances have led to the accumulation of genetic elements that favor either silencing or escape; lack of dosage sensitivity might also allow for the escape of flanking genes near another escapee, if a boundary element is not present between them. Delineation of the elements involved in escape is progressing, but mechanistic understanding of how they interact to allow escape from XCI is still lacking. Although increasingly well-studied in humans and mice, non-trivial challenges to studying escape have impeded progress in other species. Mouse models that can dissect the role of the sex chromosomes distinct from sex of the organism reveal an important contribution for escape genes to multiple diseases. In humans, with their elevated number of escape genes, the phenotypic consequences of sex chromosome aneuplodies and sexual dimorphism in disease both highlight the importance of escape genes.